ANALISIS KADAR FLAVONOID DAN FENOLIK TOTAL FRAKSI ETIL ASETAT DAUN KETEPENG CINA (Senna alata (L.) Roxb) DENGAN METODE SPEKTROFOTOMETRI UV-VISIBLE - Rahmawati Rahmawati; A. Muflihunna; A. Trihadi Kusuma (Fakultas Farmasi UMI, 2015)
Analysis of flavonoid and phenolic content of ethyl acetate fraction have done in chinese ketepeng leaves (Senna alata (L.) Roxb) using UV-Visible spectrophotometric method. This research aimed to analyzed of flavonoids and phenolic content of ethyl acetate fraction of chinese ketepeng leaves. Chinese ketepeng leaves were extracted using ethanol 96%, and then were partitioned using a liquid-liquid partition method of ethyl acetate to obtain ethyl acetate fraction. Flavonoid and phenolic content determined using UV-VIS spectrophotometric at 415 nm wavelength for flavonoid and 730 nm for phenolic. This research results showed that the flavonoid content of ethyl acetate fraction of chinese ketepeng leaves is 2,665 mgRE/g and phenolic content of ethyl acetate fraction of chinese ketepeng leaves is 3,729 mgRE/g.